2005
DOI: 10.1016/j.jacc.2005.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Coronary In-Stent Restenosis With Multidetector Row Spiral Computed Tomography

Abstract: In-stent restenosis can be diagnosed with moderate sensitivity using a new generation 40-slice MDCT scanner. The high NPV implies a significant role for MDCT in excluding ISR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 16 publications
(6 reference statements)
4
66
0
4
Order By: Relevance
“…Unfortunately, only 72% of all stented vessels were assessable in study populations. Recently, Gaspar et al (48) attempted to assess the efficacy of 40-slice MDCT in similar evaluations of post-PCI restenosis. This study found that 96% of stented vessels could be assessed by 40-slice MDCT.…”
Section: Assessment Of In-stent Restenosis Using Mdctmentioning
confidence: 99%
“…Unfortunately, only 72% of all stented vessels were assessable in study populations. Recently, Gaspar et al (48) attempted to assess the efficacy of 40-slice MDCT in similar evaluations of post-PCI restenosis. This study found that 96% of stented vessels could be assessed by 40-slice MDCT.…”
Section: Assessment Of In-stent Restenosis Using Mdctmentioning
confidence: 99%
“…For example, thick-strut stents (>140 μm) are reported to have low sensitivity on MDCT as compared with thin-strut stents (<140 μm). [20][21][22][23] Another report suggested that tantalum, gold or gold-coated stents, and covered stent grafts had reduced visualization of the lumen compared with stainless steel or cobalt stents. 24 The present study included both 2.25-mm and 2.5-mm stents (a total of 105/33.2%), classified as small stents, but Cypher stent was used at a high rate (62.3%), these being made of stainless steel, but with a strut thickness of 140 μm which provides severe artifacts on evaluation of the in-stent lumen.…”
Section: Discussionmentioning
confidence: 99%
“…The stent struts create a blooming artefact which makes the stent struts much larger, thereby obscuring part of the in-stent lumen. Stent evaluation is usually limited to the assessment of stent patency which is quite reliable, but in particular, the smaller sized stents (≤ 3mm in diameter) do not permit evaluation of the presence of neo-intimal hyperplasia or in-stent restenosis (41)(42)(43)(44)(45) .…”
Section: Ct-coronary Angiography For Assessment Of Coronary Stentsmentioning
confidence: 99%